Risk of developing cardiovascular diseases on radiation exposure to thoracic region: a review - Mazumder, Dhrubanil (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.